The Reality of Nursery and kindergarten Organizational Manual Application by Kindergarten Female Principals in Jeddah Governorate - Alghamdi, Tahani Saud Eid; Alsanat, Aljawharah Ibrahim (Journal of Educational and Psychological Sciences, 2020)
The current research aimed at recognizing the reality of female kindergarten leaders' application of the organizational guide of nursery and kindergarten schools in Jeddah Governorate. The researcher adopted the descriptive survey and the descriptive comparative approaches. A questionnaire was used as a research tool that was distributed to a sample of female public kindergarten teachers (n = 212). The results concluded that the reality of female kindergarten leaders' application of the organizational guide of kindergarten schools in Jeddah Governorate from the female teachers' perspective had a general mean (3.53 out of 5), which is a high score. At the level of dimensions, the dimension of female leaders' duties had a mean (3.72), followed by the dimension of kindergarten assemblies and committees with a mean of (3.57) which is also considered a high score. Finally, the functional kindergarten formations came with a mean of (3.29) which is a (moderate) score, whereas the suggestions dimension had a mean of (3.46) which is a (high) score. Additionally, there were statistically significant differences between the mean responses of sample individuals concerning the total score of reality of female kindergarten leaders' application of the organizational guide of kindergarten schools and the sub-dimension (functional kindergarten formations) in favor of those whose years in service were (10) years and more. Based on the research findings, the researcher introduced many recommendations, the most prominent of them were: holding training programs and workshops for female kindergarten leaders in Jeddah Governorate about applying the organizational guide, especially with regard to functional kindergarten formations, and providing financial and moral incentives for female kindergarten leaders who apply the organizational guide.
Keywords: Female kindergarten leaders; organizational guide; kindergarten; Jeddah Governorate